Hydrothermal areas, microbial mats and sea grass in Paleochori Bay, Milos, Greece. Issue 2 (9th December 2020) - Khimasia, Anant; Rovere, Alessio; Pichler, Thomas
ABSTRACT: The study presents a 1:3300 scale map, encompassing an area of 1.05 km 2, depicting the first detailed map of the shallow-water water hydrothermal system in Paleochori Bay, Milos, Greece. The seafloor was mapped using orthophotos acquired by a drone survey and processed using ArcGIS. The map shows the distribution of white microbial mats, former microbial mats, sea grass and 'normal' sand down to a depth of 15 m. Generation of a comprehensive map with native shapefiles and layer files, where any GPS coordinate in Paleochori Bay can be obtained, allows to target specific locations for data collection, rather than resorting to vague site descriptions, as has been the practice in the past. Sea floor temperature measurements carried out by Scuba divers in conjunction with GPS coordinates were mapped and interpolated to evaluate the temperature distribution in Paleochori Bay, which in turn supports the overall understanding of the hydrothermal system.